2014
DOI: 10.12816/0008217
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Chromosomal Association in Kidney Bean ( Phaseolus Vulgaris L. )

Abstract: The present study documents the mutagenic efficacy of gamma ray and sodium azide on the chromosomal association pattern of bivalents and meiotic behavior in Phaseolus vulgaris L. The seeds were irradiated with different doses of gamma rays viz.10 krad, 20 krad, and 30 krad from a 60 Co source and thereafter, the seeds were treated with 0.3% of freshly prepared sodium azide solution for three hours, respectively. The results clearly show the formation of various types of secondary chromosomal association among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Secondary associations were first described by Lawrence (1931) and were thereafter regularly referred to in meiotic studies of several plant species, most of them about polyploid species (Gustafsson 1935;Kempanna and Riley 1964;Kumar and Singhal 2013), including sugarcane (Sreenivasan and Jagathesan 1975). Such associations were also described in haploids (Sadasivaiah and Kasha 1971;Jelenkovic et al 1980), in material exposed to ionizing radiation and mutagenic treatments (Kumar and Chaudhary 2014) and even in the ancestral polyploid Brassica oleracea (Wills 1966;Ji et al 2014). Although the nature for such associations may be different in the examples mentioned above, the general clarification for this phenomenon points at residual homology or duplicated segments between homeologous and non-homologous chromosomes as found in (ancestral) polyploids and haploids, respectively (Kempanna and Riley 1964).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Secondary associations were first described by Lawrence (1931) and were thereafter regularly referred to in meiotic studies of several plant species, most of them about polyploid species (Gustafsson 1935;Kempanna and Riley 1964;Kumar and Singhal 2013), including sugarcane (Sreenivasan and Jagathesan 1975). Such associations were also described in haploids (Sadasivaiah and Kasha 1971;Jelenkovic et al 1980), in material exposed to ionizing radiation and mutagenic treatments (Kumar and Chaudhary 2014) and even in the ancestral polyploid Brassica oleracea (Wills 1966;Ji et al 2014). Although the nature for such associations may be different in the examples mentioned above, the general clarification for this phenomenon points at residual homology or duplicated segments between homeologous and non-homologous chromosomes as found in (ancestral) polyploids and haploids, respectively (Kempanna and Riley 1964).…”
Section: Discussionmentioning
confidence: 85%
“…Klášterská (1976) argued that such threads in multivalent-like associations as found in Rosa meiosis are the result of a disturbed recondensation of the chromosomes after the diffuse diplotene stage and do not reflect any kind of structural hybridity. However, as strong variation in such associations was found between the samples from different seasons it may suggest that environmental conditions play a role in the occurrence of such secondary associations, an explanation that is also favored by Kumar and Chaudhary (2014). Alternatively, Thomas andRevell (1946), andJelenkovic et al (1980) suggested that duplications in the heterochromatic segments favors associations between non-homologous parts, which find support in the recent FISH study of Brassica oleracea meiosis (Ji et al 2014) showing that such inter-bivalent connections contain stretches of 45S rDNA and centromere tandem repeats.…”
Section: Discussionmentioning
confidence: 99%
“…More than century ago the phenomenon of secondary associations was discovered by TAHARA (1909) in Morus (1909). Subsequently, this phenomenon had been reported by many other workers (KUWADA, 1910;ISHIKAWA, 1911;MARCHAL, 1912;DARLINGTON, 1928;LAWRENCE, 1931;HEILBORN, 1936;JACOB, 1957;GUPTA and ROY, 1973;AGARWAL, 1983;ARGIMYN et al, 1999;KUMAR et al, 2013;KUMAR and CHAUDHARY, 2014). Different views applied by different authors to explain the basis of secondary associations include, the fusion between heterochromatic regions of the involved bivalents (THOMAS and REVELL, 1946), homology of paired bivalents, and artefact induced due to squash technique (HEILBORN 1936;BROWN, 1950) or fixation (PROPACH, 1937).…”
Section: Methodsmentioning
confidence: 85%